ETIKA DAN DAMPAK SOSIAL DARI PENERAPAN ARTIFICIAL INTELLIGENCE DALAM SISTEM INFORMASI MANAJEMEN - Tri Setia Ningrum; Vika Dias Anspratiwi; Muhamad Wahyudi (Jurnal Riset Sistem Informasi, 2025)
The application of artificial intelligence in management information systems provides effectiveness and efficiency in business processes. The integration of artificial intelligence and management information systems has changed the procedures for collecting data, analyzing data, and utilizing data. This research aims to explain the application of artificial intelligence in management information systems and identify ethical challenges and social impacts arising from the application of artificial intelligence in management information systems. The research method used in this research is the library study method, which is a research approach that involves collecting and analyzing information available in forms such as articles, reference books and other reference sources. The results of the research are that the application of artificial intelligence provides convenience by automating routine tasks thereby increasing user efficiency and effectiveness. However, apart from providing convenience, there are ethical challenges and social impacts that arise from the application of artificial intelligence in management information systems, such as threats to data security and increasingly narrow job opportunities.